THE EFFECT OF THE PRINCIPAL LEADERSHIP, SCHOOL CULTURE, AND TASK COMMITMENT TO QUALITY OF SERVICE VOCATIONAL HIGH SCHOOL TEACHERS IN THE BOGOR REGION - BUTAR, CHARLES BUTAR (PPs UNJ, 2016)
The objective of this research is to study the effect of the principal leadership, school culture, and task commitment to quality of service vocational high school teachers in the Bogor region. Quantitative approach used in this research with survey method. The samples of this research were one hundred and thirty one teachers and student selected randomly. The research was conducted on quality of service teacher involving samples of 194 teacher had been selected from the target population of 131 teacher in the Bogor Region by using quantitative approach with path analysis methodes. The data were obtained by distributing questionnaire and analyzed by using path analysis. The result of the research can be conclude that: 1) the principal leadership, school culture and task commitment had a positive direct effect on quality of service teacher; 2) the principal leadership and shool culture had a positive direct effect on task commitment teacher.Therefore to improve quality of service, the principal leadership, school culture, and task commitment should be improved vocational high school teachers in the Bogor region . Implications and limitations of the study are discussed along with suggestions for future research.